Inovasi dalam Produksi Official Statistic: Tantangan dan Peluang - Muh. Dzulrian (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In most countries, the national authority is responsible for systematically and regularly collecting, processing, and publishing numerical information, or statistics, on various phenomena that affect the development and well-being of society. These statistics, known as Official Statistics, are intended to depict the demographic, economic, ecological, and social developments of a country. However, the process and production of Official Statistics have undergone significant modernization due to technological advancements, cost reductions, and the emergence of digital platforms. This article aims to identify challenges and opportunities for innovation in the production of Official Statistics. The method employed in this article is a conceptual method. The importance of data collection and analysis is immense for the National Statistical Office (NSO), but the scope of data regulation and privacy is still limited. The increased use of big data and digital data also contributes to the modernization of Official Statistics.